2009
DOI: 10.1017/s1368980008003662
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality: associations with health messages included in the Danish Dietary Guidelines 2005, personal attitudes and social factors

Abstract: Objective: To study the association between diet quality and the new health messages in the Danish Dietary Guidelines 2005, i.e. 'Eat a varied diet', 'Engage in regular physical activity' and 'Maintain a healthy body weight'. Design/setting/subjects: The study was cross-sectional, comprising a random sample of 3151 Danish adults aged 18-75 years. Dietary intake was estimated using a 7 d pre-coded food diary. Information on social background, leisure-time physical activity, height, body weight and intention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It can also modify the association between SEP and diet [ 44 , 48 ]. Attitudes towards health benefits of diet and awareness of key messages may lead high educated persons to comply better with dietary recommendations [ 49 ] by consuming less animal products and more wholegrain foods and fruit and vegetables, the main sources of fibre in France and contributors to vitamin C and beta carotene intakes [ 8 , 10 , 44 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can also modify the association between SEP and diet [ 44 , 48 ]. Attitudes towards health benefits of diet and awareness of key messages may lead high educated persons to comply better with dietary recommendations [ 49 ] by consuming less animal products and more wholegrain foods and fruit and vegetables, the main sources of fibre in France and contributors to vitamin C and beta carotene intakes [ 8 , 10 , 44 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to external eating, the studies that have been conducted yielded mixed findings: some studies showed that men score higher than women (15,16) while others showed similar scores for men and women (8,13) . With regard to the intention to eat healthily, the limited studies that have been conducted seem to suggest that women have stronger intentions to eat healthily than men (20) . Nevertheless, this stronger intention might not necessarily be beneficial as it has also been suggested that women's motivation to eat a healthy diet masks concern about their appearance (21,22) rather than their health, which may actually lead to unhealthy eating patterns (23)(24)(25) .…”
mentioning
confidence: 99%
“…However, our results can be linked to previous data showing that an individual's concern about nutrition is positively related to the nutritional quality of the diet. In particular, several studies showed that a higher importance assigned to healthy eating was positively associated with adherence to dietary recommendations (41,42) , as well as intake of fruit and vegetables (43)(44)(45)(46)(47) , and fibres (46) , whereas it was negatively associated with saturated fat intake (46) . In addition, health interest has been previously described as the most significant reason for reducing meat and meat products in the diet (48) , thus supporting our results.…”
Section: Discussionmentioning
confidence: 99%